Assessing the role of off‐take and source–sink dynamics in the extinction of the amphidromous New Zealand grayling (Prototroctes oxyrhynchus). (19th July 2019) - Lee, Finnbar; Perry, George L. W.
Abstract: Some extinctions have obvious drivers (e.g. over‐harvesting), while others can be less obvious and arise from multiple interacting factors. The extinction of the New Zealand grayling ( Prototroctes oxyrhynchus ) has been blamed on over‐fishing and predation by introduced trout, but these explanations fail to account for the species disappearance from isolated, uninvaded rivers. We investigated if source–sink dynamics, facilitated by P. oxyrhynchus 's amphidromous dispersal habit, could account for the species' rapid extinction. We created a database of P. oxyrhynchus sightings by surveying newspapers dating back to 1839, along with a review of traditional scientific literature. We used this database to update P. oxyrhynchus 's known distribution map and inform sighting models to predict P. oxyrhynchus 's extinction date. Finally, we implemented a meta‐population model to explore how source–sink dynamics could interact with off‐take (over‐fishing or predation) to drive extinction. Prototroctes oxyrhynchus was found across New Zealand, except the north of the North Island. Based on sightings methods, the earliest predicted extinction date was 1924, although the species may have persisted until 1972, later than previous estimates have suggested. In the absence of source–sink dynamics, relatively high levels of off‐take were sustainable (up to 30% per generation). When the species was modelled as a panmictic meta‐population including 5% sink habitats, the sustainable off‐take rate was reduced to as low as 5% per generation. Prototroctes oxyrhynchus was a widespread, abundant species that underwent rapid declines and ultimately went extinct. Previous attempts to explain this extinction have failed to account for the species extinction from isolated, pristine rivers. Our modelling shows that treating the species as a panmictic metapopulation and including source–sink dynamics rapidly increases the probability of extinction. We suggest that source–sink dynamics may be an important aspect of the population dynamics of amphidromous species and should be considered when managing taxa with similar dispersal habits.